Cover Picture: Plasma Process. Polym. 12∕2015. Issue 12 (December 2015) - Ueda, Masashi; Yamagami, Daiki; Watanabe, Keiko; Mori, Asami; Kimura, Hiroyuki; Sano, Kohei; Saji, Hideo; Ishikawa, Kenji; Hori, Masaru; Sakakita, Hajime; Ikehara, Yuzuru; Enomoto, Shuichi
Abstract : Front Cover: Bleeding from vessels in clinical practice is controlled by cauterization with a thermal coagulator (TC). However, the mechanical contact and heat produced by the TC injures tissues and causes long‐lasting infl ammation (upper panel). In contrast, hemostasis with non‐thermal plasma (NTP) does not induce tissue damage. Positron emission tomography imaging with 18 F‐FDG, which is a radiopharmaceutical targeting infl ammation, noninvasively reveals that less invasiveness of hemostasis with NTP (lower panel). Further details can be found in the article by Masashi Ueda et al.on page 1338 .